Hazardous Effects of Sucralose and Its Disinfection Byproducts Identified From an E. coli Whole-Cell Array Analysis - Zhai, Yuanxin; Bai, Dan; Yang, Heyun; Li, Xiaoliang; Zhu, Daiwen; Cao, Xin; Ma, Hao; Li, Xiaolin; Zheng, Xing (Frontiers in Environmental Science, 2021)
In this study, an E. coli whole-cell microarray assay was used to evaluate the impact of sucralose (SUC) on 110 selected genes under different exposure concentrations. Further, toxicity caused by SUC under five disinfection processes was explored. Our results revealed detailed transcriptional information for gaining insights into the toxicity mechanism. SUC at lower concentrations tends to induce more protein response, while greater DNA damage occurs at higher concentrations. In addition, SUC could induce changes in expression of various genes, with the DNA damage exhibiting an obvious concentration-dependence. As the exposure concentration of SUC increases, stress is transformed from a single type level to the entire system, which could enhance cellular ability to resist damage and survive. Exposure-recovery tests show long-term exposure (24 h) to SUC causes irreversible damage, and at SUC concentrations of 103-104 mg/L, short-term exposure (2 h) exerts the same effect. Further, SUC toxicity is enhanced on disinfection, with ultraviolet light causing particularly serious DNA damage.